Dynamic Changes in the Global Transcriptome and MicroRNAome Reveal Complex miRNA-mRNA Regulation in Early Stages of the Bi-Directional Development of Echinococcus granulosus Protoscoleces - Bai, Yun; Zhang, Zhuangzhi; Jin, Lei; Zhu, Yongqiang; Zhao, Li; Shi, Baoxin; Li, Jun; Guo, Gang; Guo, Baoping; McManus, Donald P.; Wang, Shengyue; Zhang, Wenbao (Frontiers in Microbiology, 2020)
Background: Cystic echinococcosis is a life-threatening disease caused by the larval stages of the dog tapeworm Echinococcus granulosus. Protoscoleces (PSCs) of this worm have the ability of bi-directional development to either larval cysts or strobilar adult worms. However, the molecular mechanisms underlying this development are unknown. Results: RNA and small RNAs sequencing were employed to characterize the gene and miRNA expression at 0h, 24h, 7d and 14d of bi-directional development by PSCs. A total of 963 genes and 31 miRNAs were differentially expressed in PSCs to adult worms development and 972 genes and 27 miRNAs to cyst development. Pairwise comparison between the two developmental patterns showed that 172 genes and 11 miRNAs were differentially expressed at three time-points. Most of these genes were temporally changed at 24h or 7d. GO enrichment analysis revealed that the differentially expressed genes in adult worm development are associated with nervous system development and carbohydrate metabolic process; whereas, the differentially expressed genes in cystic development are associated with transmembrane transporter activity and nucleoside triphosphatase activity. In addition, miR-71 and miR-219 regulated genes are likely involved in oxidation reduction in the adult worm development. Conclusions: Bi-directional development of E. granulosus PSCs is controlled by miRNAs and genes likely associated with nervous system development and carbohydrate metabolic process. ATP-dependent transporter genes are associated with cystic development. These results may be important for exploring the mechanisms underlying E. granulosus development, providing novel information governing the development of new therapeutics for controlling cystic echinococcosis.